Kontribusi Sosial Terkait Menumbuhkan Keberpihakan dan Kepedulian Terhadap Sesama dengan Semangat Kebhinekaan - Mutmainnah (Lembaga Penelitian dan Pengabdian Masyarakat, 2024)
This social contribution aims to (1) foster a sense of caring and a spirit of sharing for students, (2) improve children's welfare: providing gifts of school equipment can help fulfill the basic needs of orphanage children, so that they can learn and grow better, (3) foster mutual care and a sense of empathy among the community, encouraging more people to engage in worthwhile social activities, (4) support education: by providing school equipment, children have the necessary tools to learn effectively. This can help improve their academic performance and motivation to learn, (5) set an example: doing positive social activities can set an example for the younger generation, inspiring them to engage in charitable activities and help others in the future.